Analisis Manajemen Laba dan Kinerja Operasi Terhadap Profitabilitas pada Perusahaan Go Public yang Melakukan Initial Public Offering (IPO) - Sulistiani, Dwi; Oktora Maha, Finta Widya (UNUSA Press, 2016)
This study aimed to determine whether the publicly traded company initial public offering (IPO) using the earnings management policies, as well as to see the effect of earnings management and operating performance on profitability in the company went public policy that performs an (IPO) in 2008. The results showed that the test is based on one- sample t test proved that the company indicated use of earnings management around IPOs. While based on paired samples t - test , and Wilcoxon signed rank the result that there are differences in operating performance and profitability of the company went public between before and after the policy does IPO. It results that the most influential variable is the current ratio dan 62% of the level of profitability of companies doing an IPO is influenced by variables of earnings management and operating performance. Through the F test can be seen that all the independent variables simultaneously affect the dependent variable. Hypothesis testing using T test showed that of the three independent variables found to significantly affect the dependent variable.